The efficacy of multiple-criteria design matrix for biodiesel feedstock selection. (15th October 2019) - Anwar, Mohammad; Rasul, Mohammad G.; Ashwath, Nanjappa
Highlights: Multiple-criteria decision analysis for screening non-edible biodiesel feedstocks. Biodiesel from stone fruit kernel oil, papaya seed oil, waste cooking oil, etc. Weightage determination methods to analyse relative importance of fuel properties. Best performing biodiesels are stone fruit oil and papaya seed oil biodiesels. Abstract: The increasing demand for energy and depletion of fossil fuels are drawing attention to biofuel as a replacement for petroleum diesel. Hundreds of non-edible biodiesel feedstocks are available and are derived from seeds and animal fat or tallow. However, the selection of appropriate feedstock is fraught with difficulty, as these feedstocks have not been fully evaluated for various parameters that impact upon the performance and cost of the biofuel. Various technical, environmental, economic and social factors influence biodiesel feedstocks selection process. This paper focuses on technical aspects such as physico-chemical properties and fatty acid compositions of biodiesels in the screening process. Six biodiesels, namely papaya seed oil biodiesel (PSO), stone fruit kernel oil biodiesel (SFO), jatropha oil biodiesel (JBD), rapeseed oil biodiesel (RBD), beauty leaf tree biodiesel (BLT), and waste cooking oil biodiesel (WCB) were analysed in this study. Twelve physico-chemical properties of kinematic viscosity (KV), density, higher heating value (HHV), oxidation stability (OS), acid value (AV), flash point (FP), cold filter plug point (CFPP), cetane number (CN), iodine value (IV), monounsaturated fatty acid (MUFA), polyunsaturated fatty acid (PUFA) and long chain saturated factor (LCSF) were selected as criteria for ranking the above biodiesels. Three weightage (%) methods of EQUAL, CRITIC and ENTROPY were used for weight determination of criteria. Four different multiple-criteria decision analysis (MCDA) methods, namely PROMETHEE Graphical Analysis for Interactive Assistance (GAIA), Weighted sum method (WSM), Weighted product method (WPM), and Technique for order preference by similarity to ideal solution (TOPSIS) were used for the analysis. Properties of these biodiesels were found to be within the limits of ASTM D6751-2, EN 14214 and the Australian standard. Finally, the results show that SFO was ranked as the best performer amongst the six biodiesel feedstocks examined in this study, PSO came out as the second best, and the WCB biodiesel feedstock was identified as the worst performer.